UJI KANDUNGAN BORAKS PADA PEMPEK LENJER YANG DIJUAL DI KELURAHAN PAHLAWAN - Irham Falahudin; Elfira Rosa Pane; Niar Kurniati (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2016)
Pempek is processing product of fish meat and tapioca flour. Pempek has a low shelf life because the process of making it that is boiled first, it makes pempek easy to be slimy. It is one of the reason why the Pempek seller uses dangerous preservative such as borax. The purpose of this research is to know whether Pempek Lenjer that is sold in Pahlawan Palembang Village contains borax or not, and contribution in the form of student worksheet (LKS) and poster. This research uses organoleptic test, then color test by using tumerik paper to know the existence of borax in Pempek Lenjer at sold in Pahlawan, Kilometer 3,5, Palembang City, South Sumatera, Indonesia. Date research on 17-24st June 2015. In this research, organoleptic test indicates that there is no Pempek Lenjer that has a characteristic containing borax, on the colour test all sampels lenjer pempek doesn’t contain borax, because it does not change color on paper tumerik that has dripped samples, performed three, and it is done validation in the student worksheet (LKS) with 5 validators from 3 schools and the result of validation of the student worksheet (LKS) from 5 validators is valid